Implementasi Deteksi Dan Koreksi Error Pada Komunikasi Serial Arduino Berbasis UART Dengan Metode Hamming Code - Anggi Fajar Andana; Sabriansyah Rizqika Akbar; Rizal Maulana (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
While error appears, it can be a mistake for the information. The emergence of error caused by many factors, for example the presence of noise in the data transmission medium, time of use of the hardware, or the quality of the hardware. One of concepts called information redudancy is a concept that inserts additional information on the process of encoding data before the data transmitted. Information Redundancy can be applied to the process of error control coding, which is technique that enables the encoding process to calculate additional control bits from the information, and to transmit these control bits and their information. In this research, using Hamming Code method to applying in Arduino and UART communication. The Hamming Code method is a method that add an additional bits to the data bit by using XOR logic on the process. In this research, Hamming code method can do the process of encode and decode, and can perform the detection and correction process on data that have errors in the testing process. The average delay for 5 bit data is 102.7m/s and 109.5m/s for 4 bit data in the encode process. In decode prosess, 17.5 m/s for 10 bit data and 100,1m/s for 11 bit data. Temperature data retrieval and the number in the encode and decode process can be a factors that greatly affect the encode and decode process using the Hamming Code method.